The protective effect of Zinc and Magnesium against subchronic Cadmium toxicity in Wistar rats (Biochemical and neurobehavioral effects) - KOUADRIA, MOHAMED; DJEMLI, SAMIR; TAHRAOUI, ABDELKRIM (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study shows the beneficial effect of (zinc 10mg / kg + magnesium 10mg / kg) against cadmium poisoning at a dose of 15mg / kg on biochemical parameters and neurobehavioral functions in Wistar rats during a period of 45 days. Methods: The experiment was carried out on 20 Wistar rats, weighing 180 to 232g for an initial weight before starting treatment with cadmium. The rats are grouped in cages at a rate of 5 in groups: Group (1) control: was supplied only with water Group (2) contaminated with cadmium (Cd): water plus oral administration cadmium dose 15mg / Kg / l. Group (3) contaminated with (Cd) dose 15mg / Kg / l in water plus magnesium (Mg) dose 10mg / Kg / l oral administration. Group (4) contaminated with (Cd) dose 15mg / Kg / l in water plus zinc (Zn) dose 10mg / Kg / l oral administration. Results: The rats exposure to cadmium showed a very highly significant decrease in body weight of cadmium-contaminated rats (P <0.001) compared with the control group. Regarding the biochemical parameters, there was a very highly significant increase (P <0.001) in the cadmium group blood glucose level compared to the control group, a highly significant increase (P <0.01) in the group urea level. cadmium compared to the control, a very highly significant increase (P <0.001) in the creatinine level of the cadmium lot compared to the control, a very highly significant increase (P <0.001) of transaminases (GOT, GPT) of the group cadmium relative to the control, complete blood count (CBC) demonstrated a very highly significant increase (P <0.001) in the white blood cell count, the hematocrit of the cadmium lot compared to the control, a very highly significant decrease (P <0.001). ) the red blood cell and hemoglobin levels of the cadmium group compared to the control. A significant improvement (P <0.001) (P <0.01) (P <0.05) of lots: zinc, magnesium, cadmium + zinc and cadmium + zinc compared to cadmium. However, the results obtained from the neurobehavioral tests reveal a significant elevation (P <0.001) (P <0.01) (P <0.05) in the number of cells crossed, the number of straightening in the test. Open field in the group exposed to cadmium resulting in locomotors hyperactivity compared to the control and it is minimal in other groups treated with zinc and magnesium. On the other hand, the plus maze (labyrinth test) revealed a very highly significant increase (P <0.001) (P <0.01) (P <0.05) of the time spent in the closed arms of the cadmium group compared to the control, a significant improvement (P <0.001) (P <0.01) (P <0.05) of the lots: zinc, magnesium, cadmium + zinc and cadmium + zinc compared with cadmium. Conclusion: Subchronic cadmium toxicity has harmful effects on the biochemical, hematological and neuro-behavioral parameters of Wistar rats, with the installation of an anxiety that will lead to a depressive state, which will be reduced and improved by the antioxidant effect of zinc + magnesium. Keywords: Cadmium-zinc-magnesium-subchronic toxicity-Wistar-Open field-plus maze